2007
DOI: 10.1093/cvr/cvm076
|View full text |Cite
|
Sign up to set email alerts
|

EMAP-II downregulation contributes to the beneficial effects of rapamycin after vascular injury

Abstract: These data suggest important yet unrecognized roles of EMAP-II and adventitial inflammation in neointima formation: Through inhibition of EMAP-II, rapamycin reduces the recruitment of inflammatory cells to the adventitia and supports an early and bland healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…36 Recently, a role of mTORC1 in inflammatory reactions and in the recruitment of HPCs to the site of vascular injury has widened the impact of mTORC1 activation in vascular remodeling and healing. 20 Taken together, the present study demonstrates a fundamental role of the Th1 immune response in repair and regeneration of vascular tissue after vessel injury yielding the CXCR3-dependent activation of mTORC1 as the interface between Th1 immune response and proliferative processes in vascular disease. These data may provide a rationale for the development of novel therapeutic strategies aiming at the inhibition of the CXCR3 axis.…”
Section: Cxcr3-dependent Activation Of Mtorc1 Is a Key Event In Ros Gsupporting
confidence: 61%
“…36 Recently, a role of mTORC1 in inflammatory reactions and in the recruitment of HPCs to the site of vascular injury has widened the impact of mTORC1 activation in vascular remodeling and healing. 20 Taken together, the present study demonstrates a fundamental role of the Th1 immune response in repair and regeneration of vascular tissue after vessel injury yielding the CXCR3-dependent activation of mTORC1 as the interface between Th1 immune response and proliferative processes in vascular disease. These data may provide a rationale for the development of novel therapeutic strategies aiming at the inhibition of the CXCR3 axis.…”
Section: Cxcr3-dependent Activation Of Mtorc1 Is a Key Event In Ros Gsupporting
confidence: 61%
“…A significant increase over time in whole lung but a decreasing trend in tracheal aspirates suggested that EMAP II expression is localized and compartmentalized in response to hyperoxia. EMAP II has been shown to augment inflammatory cell counts (34). We proposed that the localization of EMAP II would be distributed in cells near the tracheal aspirate collection site and thus, histological analysis by co-staining .…”
Section: Emap II Levels In Lung Disease Of Prematuritymentioning
confidence: 99%
“…In the vasculature, EMAP II is increased after percutaneous coronary intervention (PCI), and EMAP II enhances the recruitment of inflammatory cells (44). Treatment with rapamycin prevents neointima formation and the increase in EMAP II expression post-PCI (27). EMAP II also inhibits angiogenesis, which can be beneficial in tumors but can be deleterious when manifest as inhibition of endothelial cell proliferation.…”
Section: Emap IImentioning
confidence: 99%